Examination of photocatalytic Z-scheme system for overall water splitting with its electronic structure. Issue 16 (6th April 2023) - Tani, Tadaaki; Yamaguchi, Yuichi; Nishimi, Taisei; Uchida, Takayuki; Kudo, Akihiko
Abstract : The STH conversion efficiency of Z-scheme system for OWS as illustrated here is the highest among photocatalyst ones and is still short for practical use. We studied the electronic structure of the system on solid state physics and proposed several new subjects to be solved. Abstract : Although the solar-to-hydrogen (STH) conversion efficiency of a photocatalytic Z-scheme system for overall water-splitting with a solid-state electron mediator composed of a hydrogen evolution cocatalyst (HEC) nanoparticles/hydrogen evolution photocatalyst (HEP) particle layer with an Rh, La-codoped SrTiO3 /conductor with an Au/oxygen evolution photocatalyst (OEP) particle layer with Mo-doped BiVO4 /oxygen evolution cocatalyst (OEC) nanoparticles reached the highest value (1.1%) in 2016, it was still insufficient for practical application, resulting in a proposal in a previous paper to develop HEP and OEP particles with longer wavelength absorption edges. While progress has been rather slow since then, the Z-scheme system has been analyzed in this paper from a new point of view, i.e., the electronic structure of the system on the basis of solid-state physics, in order to seek for new ideas to enhance its STH conversion efficiency. In addition to the proposal in the previous paper, new ideas in this paper include the formation of a built-in potential to enhance electron (positive hole) transfer from the HEP (OEP) to the HEC (OEC) by putting positive (negative) charges on the HEC (OEC) nanoparticles, enhancement of the reduction (oxidation) of water by an electron (a positive hole) transferred from the HEP (OEP) to the HEC (OEC) by using the quantum-size effect of HEC and OEC nanoparticles, enhancement of the transfer of a photo-created positive hole (electron) from the HEP (OEP) to the conductor by controlling the Schottky barrier between them, and enhancement of the movement of electronic charge carriers together with depression of their recombination in highly doped HEP and OEP particles by the use of ionic relaxation processes in the particles.